2018
DOI: 10.1080/13607863.2018.1471585
|View full text |Cite
|
Sign up to set email alerts
|

Strengths in older adults: differential effect of savoring, gratitude and optimism on well-being

Abstract: These results represent an important step in understanding what type of strengths work best when it comes to enhancing well-being in older adults and consequently helping them tackle the challenges of everyday life and recover as quickly as possible from the adverse situations and events that may arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 52 publications
3
43
0
1
Order By: Relevance
“…While no significant pairwise correlations with HB, LS, and happiness were found, optimism predicted LS in our model [ 44 , 45 , 52 ]. Consistent with this unexpected finding for optimistic expectancies, a previous study showed that an intervention focused on increasing optimism did not reveal any effect on SWB among Spanish older adults [ 84 ]. Consequently, future research on the role of optimism for SWB in late adulthood is warranted.…”
Section: Discussionsupporting
confidence: 75%
“…While no significant pairwise correlations with HB, LS, and happiness were found, optimism predicted LS in our model [ 44 , 45 , 52 ]. Consistent with this unexpected finding for optimistic expectancies, a previous study showed that an intervention focused on increasing optimism did not reveal any effect on SWB among Spanish older adults [ 84 ]. Consequently, future research on the role of optimism for SWB in late adulthood is warranted.…”
Section: Discussionsupporting
confidence: 75%
“…In line with our hypothesis and the previous results (Jang et al, 2007;Javanmard, 2013;Park, 2007;Reis et al, 2017;Salces-Cubero et al, 2019;Silberman, 2005;Zábó et al, 2019), the inclusion of transcendence relates positively to global wellbeing, savoring, and resilience. Thus, inclusion of transcendence induces bigger fulfilment in the bio-, psycho-, socio-, and spiritual aspects of one's life.…”
Section: Discussionsupporting
confidence: 93%
“…Interventions training older adults to use specific strengths, such as humour and optimism, have demonstrated some improvements in well-being (Salces-Cubero, Ramirez-Fernández, & Ortega-Martínez, 2019), as have other studies integrating strength components (Bartholomaeus, Van Agteren, Iasiello, Jarden, & Kelly, 2019;Ho, Yeung, & Kwok, 2014).…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Proyer, Gander, Wellenzohan, and Ruch () have started to fill the gap in this evidence, finding positive outcomes in older adults who are using their signature strengths ‘in a new way’. Interventions training older adults to use specific strengths, such as humour and optimism, have demonstrated some improvements in well‐being (Salces‐Cubero, Ramirez‐Fernández, & Ortega‐Martínez, ), as have other studies integrating strength components (Bartholomaeus, Van Agteren, Iasiello, Jarden, & Kelly, ; Ho, Yeung, & Kwok, ).…”
Section: Introductionmentioning
confidence: 99%